Characterization of pedestal burst instabilities during I-mode to H-mode transition in the EAST tokamak. (1st June 2022) - Zhong, X.M.; Zou, X.L.; Liu, A.D.; Song, Y.T.; Zhuang, G.; Li, E.Z.; Zhang, B.; Zhang, J.; Zhou, C.; Feng, X.; Duan, Y.M.; Ding, R.; et al.
Abstract: Quasi-periodic pedestal burst instabilities (PBIs), featuring alternative turbulence suppression and bursts, have been clearly identified by various edge diagnostics during I-mode to H-mode transition in the EAST Tokamak. The radial distribution of the phase perturbation caused by PBI shows that PBI is localized in the pedestal. Prior to each PBI, a significant increase of density gradient close to the pedestal top can be clearly distinguished, then the turbulence burst is generated, accompanied by the relaxation of the density profile, and then induces an outward particle flux. The relative density perturbation caused by PBIs is about 6%–8%. Statistic analyses show that the pedestal normalized density gradient R / L n triggering the first PBI has a threshold value, mostly in the range of 22–24, suggesting that a PBI triggering instability could be driven by the density gradient. And R / L n triggering the last PBI is about 30–40 and seems to increase with the loss power and the chord-averaged density. In addition, the frequency of PBI is likely to be inversely proportional to the chord-averaged density and the loss power. These results suggest that PBIs and the density gradient prompt increase prior to PBIs can be considered as the precursor for controlling I–H transition.